Making Computers Do More with Less. - Santini, Simone (Computer (00189162), 2007)
Modern personal computing can be frustrating. Operating systems and programs are complicated, and can interact with each other in unpredictable ways. The author presents his ideas on how to simplify. Operating systems should be small, simple, and efficient, occupying no more than 100 Mbytes. Simple menus and a black & white should be the rule, although color can be an option for those who need it. Installing and uninstalling software should involve nothing more than copying and erasing files. Applications should be small and equipped with keyboard commands.